Avaliação da percepção e satisfação com a imagem corporal entre adolescentes brasileiros - Rocha, Ryvanne Paulino (2021)
The body image dissatisfaction usually starts in adolescence and can harm a subject’s psychological well-being in the next stages of development, also strongly linked to unfavorable behavior and attitudes towards health, such as unhealthy eating, physical inactivity, overweight, eating disorders, use of alcohol, tobacco and other drugs that can result in irreparable negative health outcomes in adulthood. In this context, nursing care can contribute to adolescent health education and promotion, especially with regard to body satisfaction and perception, with due attention to the most vulnerable group. The objective is to assess the perception and satisfaction with the body image of Brazilian adolescents in the 8 th year of public schools and factors associated with dissatisfaction with their body image. This is a cross-sectional study, draw in a randomized controlled trial to evaluate a drug use prevention program in schools. The sample consisted of 5,213 students, aged 12 to 14 years, from 73 Brazilian schools in the cities of Fortaleza, Eusébio and São Paulo, using a self applied survey, with body satisfaction being the outcome, and as explanatory variables, drug use and sociodemographic data. Weighted multinomial logistic regression was performed. Almost 70% reported body dissatisfaction, mainly because of overweight. Dissatisfaction with overweight was higher in girls (41.5%) than in boys (35.7%), while underweight was higher in boys (33.1%) than in girls (29.9%). Being a girl increased the chances of dissatisfaction due to overweight by 24% (OR=1.24). In contrast, adolescents who used marijuana were 39% (OR=1.39) more likely to be dissatisfied with underweight. The study results allow us to know the factors related to body dissatisfaction among adolescents, identifying situations of vulnerability, contributing to the direction of health education actions and specific public policies in the prevention of risky behavior, whether in drug use or other negative outcomes of health. At the end, the prevalence of body dissatisfaction among adolescents is evidenced, reflecting differently between boys and girls. Thus, it reinforces the possibility of nursing work in this context and the importance of attention to programs and public policies for the prevention and promotion of the health of adolescents that encourage positive perceptions of self-image and better self-acceptance in order to promote healthy youth and minimize outcomes negative.